Tax Understanding And Compliance Of Malay Civil Servants In Peninsular Malaysia - Yusoff, Siti Norfazlina (2020)
Paying tax is mandatory on all earning citizens. Even though many people complain about the tax levied by the government, collecting these taxes is vital for the national economy. The taxation principles emphasize that taxes should generate revenue for the provision of essential public services, and importantly, it must be shared with as much of the population and sectors of the economy as possible. Given its importance, the issue of tax compliance among individual taxpayers is a major concern since it affects the amount of income tax collected, and also taxpayers’ spending. Income tax collection has the potential to decrease people spending, because taxes will reduce disposable income. The growth of non-compliant taxpayers across employment underscores the gravity of the issue. This can be seen through the implementation of strict punishments, including harsh penalties for underreporting, and criminal prosecution against non-filers of tax returns. Therefore, the purpose of this study is to assess the taxpayers’ understanding of income tax payment, taxpayers’ e-Filing readability levels, taxpayers’ income tax declaration, the level of individual tax compliance and factors which affect their compliance level. This study employs a questionnaire as an instrument to collect responses from Malay civil servants. A total of 1000 online surveys was distributed to Malay civil servants in Peninsular Malaysia. Logit and ordered logit analysis were used to assess the income tax declaration and tax compliance levels.